COMPARATIVE STUDY BETWEEN POSTOPERATIVE ANALGESIC EFFECTS OF ADDING INTRAINCISIONAL MEPERIDINE VERSUS INTRAINCISIONAL TRAMADOL TO BUPIVACAINE IN ELECTIVE CESAREAN SECTION UNDER SPINAL ANESTHESIA - Mahmoud Ahmed Abdel Salam; Medhat Helaly Allam; Mohamed Mohamed Abo Elenin; Mohammed Al-Saeed Abdo Abu Hatab (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Background: Analgesic treatment has traditionally focused on central mechanisms associated with pain perception via the use of opioids. The aim of this work was to evaluate the postoperative analgesic effect of intra-incisional infiltration of meperidine added to bupivacaine versus tramadol added to bupivacaine in elective cesarean section (CS) under spinal anaesthesia.Methods: This randomised controlled double blinded work had been conducted on 90 healthy full-term patients aged from 20 to 35 years old, planned for elective CS under spinal anaesthesia. Patients were divided into three equal groups: Meperidine Group: obtained 50 mg meperidine with 50 mg bupivacaine, Tramadol Group: received 50 mg tramadol with 50 mg bupivacaine and Bupivacaine Group: obtained 50 mg bupivacaineResults: The amount of morphine given postoperative was significantly decreased in meperidine group and tramadol group than bupivacaine group (P≤0.001). The time of first dosage of morphine given postoperatively had been earlier in bupivacaine group contrasted to tramadol group than meperidine group (P